2014
DOI: 10.1111/epp.12102
|View full text |Cite
|
Sign up to set email alerts
|

The invasive Impatiens glandulifera Royle (Himalayan balsam) in the Republic of Macedonia: first record and forecast

Abstract: A population of Impatiens glandulifera Royle, an invasive plant species native to the Western Himalayas, was recorded in 2013 near the village Gorno Sedlarce in the north‐western mountainous region of the Republic of Macedonia. I. glandulifera is a new alien species to the Macedonian flora. The surveys revealed an intensive growth and a low to medium density population of I. glandulifera. The population's density was not quantified, but several stands of different sizes were found. A rapid ecological risk asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…The species is largely absent from truly Mediterranean vegetation types. The species has recently also spread in the Balkans and the Caucasus (Fayvush and Tamanyan, 2011;GBIF Secretariat, 2019;Komzha and Popov, 1990;Pacanoski and Saliji, 2014), and is naturalized in Russia (European part, far East and, recently, the Altai Republic), China (Hunan), Japan, New Zealand, Argentina and both western and eastern Canada and USA (Fig. 3A) (Artemov and Zykova, 2019;CABI, 2020;Čuda et al, 2020;EPPO, 2020;GBIF Secretariat, 2019;Vinogradova et al, 2020).…”
Section: Distribution and Invasion Historymentioning
confidence: 99%
“…The species is largely absent from truly Mediterranean vegetation types. The species has recently also spread in the Balkans and the Caucasus (Fayvush and Tamanyan, 2011;GBIF Secretariat, 2019;Komzha and Popov, 1990;Pacanoski and Saliji, 2014), and is naturalized in Russia (European part, far East and, recently, the Altai Republic), China (Hunan), Japan, New Zealand, Argentina and both western and eastern Canada and USA (Fig. 3A) (Artemov and Zykova, 2019;CABI, 2020;Čuda et al, 2020;EPPO, 2020;GBIF Secretariat, 2019;Vinogradova et al, 2020).…”
Section: Distribution and Invasion Historymentioning
confidence: 99%
“…A good model system to study plant species × ecosystem interactions is Impatiens glandulifera. Originating from the Himalayan Mountain ranges, it now occurs all over Europe over a broad range of elevation, geographical latitude, and ecosystem types (Pyšek and Prach 1995, Larsson and Martinsson 1998, Kollmann and Bañuelos 2004, Pacanoski and Saliji 2014, Laube et al 2015. After introduction to Europe in the 19 th century it spread mainly along riverbanks and into wet habitats such as fens, mesotrophic grasslands, and woodland, but also forests out of the riparian zone, and into ruderal vegetation (Beerling and Perrins 1993, Pyšek and Prach 1993, 1995, Čuda et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, I. glandulifera is widespread along river systems in 23 European countries, being the third most important neophyte plant in Germany (Sheppard et al, 2006). Since 2004, it has been considered an invasive species in North America and Europe and recognised in the EPPO List of Invasive Alien Plants (Pacanoski and Saliji, 2014), causing detrimental effects on native plant species through competition for space and nutrients, as well as monopolisation of pollinators (Chittka and Schürkens, 2001). In phytochemical studies, naphthoquinones have been identified as potential growth inhibitors produced by this plant (Ruckli et al, 2014).…”
Section: Introductionmentioning
confidence: 99%